Adolescents’ Language and Digital Literacy: Encoding Analysis of Students’ Responses to A Tiktok Hoax - Eva Leiliyanti; Rohmah Nur Romadhonia; Arif Muhammad Iqbal (Masyarakat Linguistik Indonesia, 2026)
This study investigates how junior high school students construct and re-encode meanings in response to misinformation about the Makan Bergizi Gratis (MBG) [Free Nutritious Meals] program on TikTok. It examines students’ encoding patterns in the comment space, the linguistic register and multimodal features they use, and how students’ perceptions of the hoax and teachers’ views on digital literacy contextualize these practices. Using a qualitative case study design, this study combines content analysis of 33 TikTok comments with online interviews conducted via Zoom and WhatsApp with ten students and five teachers. Inductive analysis shows five encoding forms: emotional expression (39%), direct criticism (33%), sarcasm/irony (9%), neutral clarification (15%), and others (3%). Linguistically, 70% of the comments used digital slang. Interviews indicate varied digital literacy, while teachers reported informal classroom integration. These findings underscore the need to strengthen school-based digital literacy education to support adolescents’ information resilience.